2014
DOI: 10.1021/am5006223
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heterocycle-Modified Pentathiophene-Based Molecular Donor Materials for Solar Cells

Abstract: Two novel solution-processable acceptor-donor-acceptor (A-D-A)-structured organic small molecules with diketopyrrolopyrrole (DPP) as terminal acceptor units and pentathiophene (PTA) or pyrrole-modified pentathiophene (NPTA) as the central donor unit, namely, DPP2(PTA) and DPP2(NPTA), were designed and synthesized. We examined the effects of changing the central bridging heteroatoms of the five-ring-fused thienoacene core identity from sulfur [DPP2(PTA)] to nitrogen [DPP2(NPTA)] in the small-molecule donor mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 70 publications
0
32
0
Order By: Relevance
“…Device performance was significantly enhanced with the use of additives. The device performance was 2.19%, with a Voc of 0.57 V, a Jsc of 9.67 mA·cm (12) with diketopyrrolopyrrole (DPP) as the terminal acceptor units and pentathiophene as the central donor unit [24]. The absorption spectra of 12 in solution showed only one main absorption band at 600 nm, indicating an intermolecular charge transfer (ICT) between the donor and acceptor units.…”
Section: Solution-processed Fused-thiophene-based Small Molecules Formentioning
confidence: 99%
See 1 more Smart Citation
“…Device performance was significantly enhanced with the use of additives. The device performance was 2.19%, with a Voc of 0.57 V, a Jsc of 9.67 mA·cm (12) with diketopyrrolopyrrole (DPP) as the terminal acceptor units and pentathiophene as the central donor unit [24]. The absorption spectra of 12 in solution showed only one main absorption band at 600 nm, indicating an intermolecular charge transfer (ICT) between the donor and acceptor units.…”
Section: Solution-processed Fused-thiophene-based Small Molecules Formentioning
confidence: 99%
“…Later, Grätzel et al group modified the anchoring group into cyano-substituted benzoic acid to make efficient sensitizers (22)(23)(24)(25)(26) [41,42]. They found that the cyano-subsituent improved the ICT and allowed for a better adsorption on TiO2, thus leading to improved DSSC performance.…”
Section: Fused-thiophene-based Sensitizers In Dye-sensitized Solar Cellsmentioning
confidence: 99%
“…In general, a potential smallmolecular donor material should possess several key properties, such as a wide and strong absorption spectrum with a large overlap with the solar emission spectrum, suitable molecular orbital energy levels matching those of acceptors and electrode, a high charge mobility, and so on [14,15]. A common strategy to enhance the PCE of OSCs is to adjust the Electronic supplementary material The online version of this article (doi:10.1007/s00894-015-2885-9) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Diketopyrrolopyrrole (DPP) has been used widely to construct conjugated polymers or small molecules as donors for OSC applications because of its strong electron-deficient property [15,17,25,26]. DPP-based small molecules with an acceptor-core-acceptor (A-core-A) structure have attracted great attention and exhibited promising PCEs [15,17,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation